Analysis of the Error Students in Solving Story Problems on Quadratic Equation Material Based on Newman Stages - Galu Parwati; Hadjar, Ibnu; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra (JTMT: Journal Tadris Matematika, 2023)
This research is a qualitative research that aims to obtain descriptive errors of students of class IXC MTs Negeri 2 Palu in solving story problems on quadratic equation material based on Newman stages. Data were collected using test and interview methods. The research subjects consisted of 1 student who made more mistakes than other students, the mistakes varied, could communicate well and get recommendations from the mathematics teacher of class IXC MTs Negeri 2 Palu. The results showed that the errors of students in class IX C MTs Negeri 2 Palu in solving story problems of quadratic equation material based on Newman's stages were (1) reading errors, namely students could not mention the unit of volume, (2) reading comprehension errors, namely students miswrote the known information from the story problem of quadratic equation material where students wrote P = 5 cm which should be P = L.+ 5 cm, (3) transform error, namely students are unable or incorrect in changing the problem into mathematical form, (4) process skill errors committed by students, namely not knowing the steps or procedures to be used in solving the story problem, (5) final answer error (encoding error), namely students incorrectly write the final answer in accordance with the desired problem